2004
DOI: 10.1093/molbev/msh050
|View full text |Cite
|
Sign up to set email alerts
|

The Melanocortin System in Fugu: Determination of POMC/AGRP/MCR Gene Repertoire and Synteny, As Well As Pharmacology and Anatomical Distribution of the MCRs

Abstract: The G-protein-coupled melanocortin receptors (MCRs) play an important role in a variety of essential functions such as the regulation of pigmentation, energy homeostasis, and steroid production. We performed a comprehensive characterization of the MC system in Fugu (Takifugu rubripes). We show that Fugu has an AGRP gene with high degree of conservation in the C-terminal region in addition to a POMC gene lacking gamma-MSH. The Fugu genome contains single copies of four MCRs, whereas the MC3R is missing. The MC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 66 publications
11
124
1
Order By: Relevance
“…Previously, the MC3Rs have been cloned from a number of species, including human (Gantz et al 1993a), rat (Roselli-Rehfuss et al 1993), mouse (Desarnaud et al 1994), and elephant (Rompler et al 2006). In lower vertebrates, the MC3Rs have been cloned from the chicken (Takeuchi & Takahashi 1999) and zebrafish (Logan et al 2003) but was found to be absent in some other fishes such as the pufferfishes (Klovins et al 2004a). The numbers we reported herein for pMC3R are roughly in line with previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, the MC3Rs have been cloned from a number of species, including human (Gantz et al 1993a), rat (Roselli-Rehfuss et al 1993), mouse (Desarnaud et al 1994), and elephant (Rompler et al 2006). In lower vertebrates, the MC3Rs have been cloned from the chicken (Takeuchi & Takahashi 1999) and zebrafish (Logan et al 2003) but was found to be absent in some other fishes such as the pufferfishes (Klovins et al 2004a). The numbers we reported herein for pMC3R are roughly in line with previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, a number of studies have been done on the pharmacological properties of mammalian (Gantz & Fong 2003), avian (Ling et al 2004), amphibian , and teleost (Klovins et al 2004a) MC1R, MC3R, MC4R, and MC5R. Collectively, these studies all show that these paralogs can all be activated by either ACTH or α-MSH with varying degrees of efficacy.…”
Section: Ligand Selectivity Of Mcrsmentioning
confidence: 99%
“…In mammals, the MC1R is expressed primarily in skin (31), where it acts directly to regulate the eumelaninpheomelanin switch (32). In contrast, MC1R expression has been reported in the brain of several fish species (33,34). AgRP2 is most potently an MC1R antagonist, with little activity at the MC4R and no activity at the MC3R (Fig.…”
Section: Melanocortin-1 Receptor Is Expressed At Highest Levels In Zementioning
confidence: 99%